Improving 3D printing laboratory operations: a case study of lean six sigma implementation - Wan, Hung-da; Castro, Octavio Zavala (BOHR International Journal of Operations Management Research and Practices, 2023)
Managing a three-dimensional (3D) printing facility was found to be more challenging than using the technology. Our research laboratory provides 3D printing services to students and faculty who need the technology to fulfill their education or research objectives. Students enrolled in Senior Design classes, in particular, rely on the availability of services to support their capstone projects. While demand increases, the laboratory becomes less efficient and sometimes chaotic. To improve the operations, Lean Six Sigma methods were applied to enhance effectiveness and efficiency. Through a DMAIC project, we enhanced the availability of resources for requestors and prevented delay or accumulation of work. The new operating procedures enabled the laboratory to provide quicker services with fewer mistakes. This case study demonstrates that Lean Six Sigma is not only useful in manufacturing but also in research and educational settings.